Cultivating wellbeing and community through writing in academia : shifting the culture with Shut Up & Write! - Lemon, Narelle (ROUTLEDGE, 2026)
This book revolutionises our understanding of academic and creative writing processes. This groundbreaking collection, the first of two volumes, explores how Shut Up & Write! (SUAW) sessions transform solitary writing into a powerful tool for community building, personal growth, and enhanced wellbeing.Featuring 17 diverse chapters from global contributors, the book unveils SUAW's evolution from a simple productivity technique to a comprehensive approach for nurturing writer wellbeing. Organised into four key sections, it examines SUAW's role in fostering community, supporting academic development, transcending institutional boundaries, and driving innovative wellbeing practices. From graduate students to established academics, university writing centres to national writers' retreats, this book offers a kaleidoscope of perspectives on implementing and adapting SUAW. It challenges the notion of writing as an isolating pursuit, instead presenting it as a collaborative, supportive endeavour that boosts creativity, builds resilience, and cultivates a sense of belonging.This essential read provides both practical strategies and theoretical insights, making it invaluable for writing program administrators, academic developers, researchers, and anyone interested in innovative approaches to supporting writers' wellbeing.
Keywords: Academic writing -- Technique.; Creative writing -- Technique.; elektronické knihy; electronic books